Impact of surface functionalization on the toxicity and antimicrobial effects of selenium nanoparticles considering different routes of entry. (October 2020) - Galić, Emerik; Ilić, Krunoslav; Hartl, Sonja; Tetyczka, Carolin; Kasemets, Kaja; Kurvet, Imbi; Milić, Mirta; Barbir, Rinea; Pem, Barbara; Erceg, Ina; Dutour Sikirić, Maja; Pavičić, Ivan; et al.
Abstract: Selenium nanoparticles (SeNPs) were first designed as nutritional supplements, but they are attractive also for use in diagnostic and therapeutic systems owing to their biocompatibility and protective effects. This study aimed to examine if different SeNPs stabilization strategies affect their (i) antimicrobial activity against bacteria Escherichia coli and Staphylococcus aureus and yeast Saccharomyces cerevisiae and (ii) toxicity to human cells of different biological barriers i.e., skin, oral and intestinal mucosa. For surface stabilization, polyvinylpyrrolidone (PVP), poly-L-lysine (PLL) and polyacrylic acid (PAA) were used rendering neutral, positively and negatively charged SeNPs, respectively. The SeNPs (primary size 80 nm) showed toxic effects in human cells in vitro and in bacteria S. aureus, but not in E. coli and yeast S. cerevisiae . Toxicity of SeNPs (24 h IC50 ) ranged from 1.4 to >100 mg Se/L, depending on surface functionalization (PLL > PAA > PVP) and was not caused by ionic Se. At subtoxic concentrations, all SeNPs were taken up by all human cell types, induced oxidative stress response and demonstrated genotoxicity. As the safety profile of SeNPs was dependent not only on target cells (mammalian cells, bacteria, yeast), but also on surface functionalization, these aspects should be considered during development of novel SeNPs-based biomedical products. Graphical abstract: Image 1 Highlights: Human toxicity and antimicrobial effects of selenium nanoparticles were studied. HaCaT, TR146 and CaCo-2 cells were chosen to represent biological barriers of entry. SeNPs are toxic to S. aureus, but not E. coli or S. cerevisiae . SeNPs show cytotoxic, genotoxic and ROS generating effects on human cells. Extent of toxicity depends on the coating agent and cell type.